2019
DOI: 10.1017/thg.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

The Guinea-Bissau Twin Registry Update: A Platform for Studying Twin Mortality and Metabolic Disease

Abstract: Sub-Saharan Africa has the highest natural twinning rate in the world. Unfortunately, due to lack of adequate care during pregnancy, labor and postnatally, twin mortality in Sub-Saharan Africa also remains very high. Thus, it has been estimated that one in five twins dies during the childhood years. In spite of this, surprisingly few twin studies have been conducted in the region, making additional epidemiological data much needed. In 2009, we established one of the first twin registries in Sub-Saharan Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This secondary analysis from the Guinea-Bissau twin registry, using previously collected data 17 , was prompted by the description of 'thin-fat' body composition of the Indian compared to the European newborns. The Indian phenotype persists in later life and is thought to result from maternal-fetal undernutrition of macro-and micronutrients 4,7,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This secondary analysis from the Guinea-Bissau twin registry, using previously collected data 17 , was prompted by the description of 'thin-fat' body composition of the Indian compared to the European newborns. The Indian phenotype persists in later life and is thought to result from maternal-fetal undernutrition of macro-and micronutrients 4,7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of previously collected (2009-2012) data from one of Africa's first twin registries set up by the Bandim Health Project (BHP) in Guinea-Bissau 19 . The BHP is a health and demographic surveillance site (HDSS), conducting epidemiological and health related research in the capital Bissau over the past 40 years.…”
Section: Cohort Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 A twin registry was set up by the Bandim Health Project (BHP, www.bandim.org) in the capital city of Bissau. 19 Follow-up of twins in this registry showed that young twins had higher plasma glucose concentrations both in fasting and in the post-glucose state compared to age-matched singletons. 20,21 This study measured skinfolds in addition to the routine anthropometry and provided an opportunity to compare adiposity of twins with that of singletons.…”
Section: Introductionmentioning
confidence: 88%
“…This is a secondary analysis of previously collected (2009-2012) data from one of Africa's first twin registries set up by the Bandim Health Project (BHP) in Guinea-Bissau. 19 The BHP is a health and demographic surveillance site (HDSS), conducting epidemiological and health related research in the capital Bissau over the past 40 years. The results of the two main metabolic twin studies have previously been reported.…”
Section: Cohort Descriptionmentioning
confidence: 99%